Firm asset size and its weathering effects to the impact of uncertainty shocks a qualitative study on publicly listed Philippine corporations - Lagos, Ralph David R. (School of Economics, University of the Philippines Diliman, 2018)
The study was conducted with the objective of evaluating the relationship of firm asset size and firm performance under the impacts of economic and financial uncertainty. It uses a mix of qualitative and quantitative analysis of standard deviations and annual growth of (1) revenues, (2) capital, and (3) earnings per share among publicly listed Philippine firms and businesses. The study concluded that larger asset sized firms within the sample were better able to weather uncertainty from the Asian Financial Crisis, Global Financial Crisis and within the period in general between 1991_2016. It also concluded that larger asset sized firms had the commonality of either being heavily diversified or being in industries with relatively inelastic demand such as utilities.